Correlation of Estimated-Glomerular Filtration Rate (e-GFR) with diabetic nephropathy and non-nephropathy patients in a tertiary care hospital (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
The estimated glomerular filtration (e-GFR) and serum creatinine is the screening methods of reduced renal function in patients with type-II diabetes (T2DM) in both patient with diabetic nephropathy and with no diabetic nephropathy. The objective of this study was to evaluate the clinical significance of e-GFR in type-II diabetes mellitus patients with diabetic nephropathy and without diabetic nephropathy.This cross-sectional study was conducted from March 2020 to February 2021 in the Department of Laboratory Medicine in collaboration with Department of Nephrology, Bangbandhu Sheikh Mujib Medical University (BSMMU), Dhaka involving 60 patients from the department of Nephrology, BSMMU. Among 60 patients, 30 were with diabetic nephropathy and 30 were without nephropathy. Both nephrop- athy and without nephropathy group were selected according to selection criteria. Random blood sugar (RBS), Glycated hemoglobin (HbA1c), serum creatinine and e-GFR level were measured in all patients. After data collection and processing, all statistical analysis was done by using SPSS Version 26.0. In this study, the mean(}SD) age was 50.5}11.71 in group-I and 45.53}9.97 in group-II. The difference was statistically not significant(p=0.082). It was observed that 20(66.7%) were male and 10(33.3%) were female in group I and 13(43.3%) were male and 17(56.7%) were female in group-II. Age group 51-60 years had highest percentage of nephropathy patients 9(30.0%) and 31-40 years of age group had highest percentage of diabet- ic patient without nephropathy 13(43.3%). The mean e-GFR in Group I was 47.56}35.48 and in Group II was 93.75}31.29 which was statistically significant (p=0.001). There was a signifi- cant negative correlation between serum e-GFR and serum creatinine in between Group I (r=-0.809, p